Production process of waterproof SPC floor

By using calcium carbonate powder and composite modified polyvinyl chloride resin as raw materials, combined with the application of nano-silica modified UV coating, the problem of insufficient waterproof performance of SPC floors is solved, and the good waterproof performance and dimensional stability of the floor in humid environments is achieved.

CN119734413AInactive Publication Date: 2025-04-01JIANGSU ZHONGXIN HOME NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510180072.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The waterproof performance of existing SPC floors is poor, mainly due to the hygroscopicity and introduction of hydrophilic components of microcrystalline cellulose, which leads to accelerated moisture penetration, limiting its application.

Method used

Calcium carbonate powder and composite modified polyvinyl chloride resin are used as the core raw materials, and the surface is formed by a twin-screw extruder, and the surface is coated with nano-silica modified UV coating, and tempered to form a hydrophobic surface to improve waterproof performance from the source.

Benefits of technology

It significantly improves the waterproof performance of SPC floors, ensures that the floor maintains good dimensional stability in humid environments, avoids moisture erosion, and improves overall environmental protection, durability and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119734413A_ABST
    Figure CN119734413A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of SPC flooring, and in particular to a production process of a waterproof SPC flooring, comprising the following steps: (1) preparation of base material; (2) high temperature extrusion molding; (3) calendering and cooling shaping; (4) surface treatment; (5) cutting and locking processing; the waterproof SPC flooring of the present invention uses calcium carbonate powder and composite modified polyvinyl chloride resin as core raw materials, eliminates the use of harmful substances such as formaldehyde and benzene from the source, and meets the strict national environmental protection standards. The SPC flooring prepared by the present invention has excellent waterproof performance during daily use, greatly prolongs the service life of the SPC flooring, and significantly reduces the maintenance cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of SPC floors, in particular to a production process of waterproof SPC floors. Background Art

[0002] SPC flooring, or Stone Plastic Composite, is a new type of environmentally friendly floor decoration material that has been widely used in the field of architectural decoration in recent years. It is mainly made of polyvinyl chloride resin and calcium carbonate powder as the basic raw materials, and is made into a base material through advanced extrusion technology, and then compounded with a colored decorative film and a wear-resistant layer.

[0003] SPC flooring has excellent environmental performance, does not contain harmful substances such as formaldehyde, benzene, etc., meets national environmental protection standards, is harmless to human health, and is suitable for use in places with high environmental protection requirements such as homes, schools, and hospitals.

[0004] Although SPC flooring performs well in many aspects, there are still some problems that need to be solved in the existing technology in terms of waterproof performance.

[0005] The substrate of the traditional SPC floor has certain limitations in raw material formula and production process, resulting in a certain water absorption. For example, the application publication number is CN113150466A, a SPC floor: "The present invention discloses an SPC floor, including an SPC floor body, the SPC floor body includes an SPC substrate layer, and the SPC substrate layer is made of the following raw materials in parts by weight: 80-120 parts of PVC resin, 200-300 parts of heavy calcium carbonate powder, 20-40 parts of nano calcium carbonate, 0.5-2 parts of lubricant, 5-10 parts of calcium zinc stabilizer, 1-5 parts of microcrystalline cellulose, and super dispersed 10-15 parts of agent, 1-3 parts of tourmaline powder, 1-10 parts of carbon nanotubes, and 1-8 parts of antibacterial agent. The SPC floor of the present invention has good tensile strength, stability, environmental protection, antibacterial property, antistatic property, air environment improvement performance, and also has a lower dimensional deformation rate and stable performance. ", its waterproof performance is relatively poor, this is because: microcrystalline cellulose is hygroscopic, the addition of cellulose materials significantly increases the water absorption rate, which may cause the floor to produce micro-swelling in an environment with a relative humidity of >75%, and the introduction of other hydrophilic components may form a water molecule migration channel, accelerate water penetration, thereby limiting its application.

[0006] Therefore, developing an SPC floor with good waterproof performance has important practical significance. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a production process for a waterproof SPC floor.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] The production process of waterproof SPC flooring includes the following steps:

[0010] (1) Preparation of base material: Calcium carbonate powder, composite modified polyvinyl chloride resin, plasticizer DOTP, calcium zinc stabilizer, and titanium dioxide are mixed in proportion to form an SPC base material mixture;

[0011] The calcium zinc stabilizer is a mixture of calcium stearate and zinc stearate in a mass ratio of 3:2;

[0012] (2) high-temperature extrusion molding: the mixed material of step (1) is melt-blended by a twin-screw extruder, extruded through a die to form an SPC substrate layer, a colored decorative film is attached to the surface, the colored film is closely attached to the substrate by hot pressing, and a wear-resistant layer is attached on the colored film, the wear-resistant layer is made of polyvinyl chloride resin and nano-alumina mixed in a mass ratio of 10:1, and a slab is obtained;

[0013] (3) Calendering and cooling: The slab prepared above is subjected to a three-roll calendering process, the roller temperature is adjusted to 110-130° C., and then cooled by a water cooling system to below 38° C.;

[0014] (4) Surface treatment: A nano-silicon dioxide modified UV coating is applied to the surface of the wear-resistant layer, and a hydrophobic surface is formed after UV curing, and then a tempering treatment is performed. During the tempering process, the hot water temperature is controlled at 80-120°C and the cold water temperature is 10°C;

[0015] (5) Cutting and locking processing: The required floor size is obtained through cutting, and a two-way locking structure is processed on the edge. After passing the inspection and packaging, the finished product is obtained.

[0016] As a further technical solution: the raw materials of the SPC substrate mixture in step (1) include, by weight: 50-60 parts of calcium carbonate powder, 20-30 parts of composite modified polyvinyl chloride resin, 5-8 parts of plasticizer DOTP, 2-4 parts of calcium zinc stabilizer, and 1-2 parts of titanium dioxide.

[0017] As a further technical solution: the preparation method of the composite modified polyvinyl chloride resin is as follows: rosin resin is crushed into particles with a particle size of less than 1 mm; rosin resin particles and polyvinyl chloride resin are added into a high-speed mixer according to a mass ratio of polyvinyl chloride resin: rosin resin of 7-10:1-3, and stirred at a speed of 600-800r / min for 5-10 minutes; maleic anhydride accounting for 1.5-2% of the mass of polyvinyl chloride resin is added, and stirring is continued for 3-5 minutes; modified copolymer toughening agent is added according to a mass ratio of polyvinyl chloride resin: modified copolymer toughening agent of 12-15:1-3, and stirred at a speed of 1200-1500r / min for 10-15 minutes; the mixed material is transferred to the hopper of a twin-screw extruder, and granulated by melt extrusion to obtain;

[0018] The specific temperature parameters of each zone of the twin-screw extruder are as follows: the temperature of the feeding section is 140-145°C, the temperature of the melting section is 180-190°C, and the temperature of the homogenizing section is 175-180°C. The twin-screw extruder is started and the screw speed is controlled at 60-70r / min.

[0019] As a further technical solution: in the step (2), the temperature of each zone of the twin-screw extruder is 155-160°C in the feeding section, 188-195°C in the melting section, and 185-190°C in the homogenizing section. The twin-screw extruder is started and the screw speed is controlled at 80r / min.

[0020] As a further technical solution: the coating amount of the nano-silicon dioxide modified UV coating in step (4) is 8-12 g / m 2 , surface contact angle after curing ≥115°;

[0021] The raw material components of the nano-silica modified UV coating include, by weight: 30-40 parts of polyurethane acrylate, 20-30 parts of active diluent, 2-4 parts of photoinitiator, and 10-16 parts of nano-silica; the active diluent is β-hydroxyethyl methacrylate, the particle size of the nano-silica is 10-20nm, and the surface is treated with a silane coupling agent KH-550, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

[0022] As a further technical solution, the UV curing process parameters are as follows: UV wavelength is 320-400nm; UV radiation intensity is 700-750mW / cm 2 ; Curing time is 15-20s.

[0023] As a further technical solution: in the step (3), the line pressure of the three-roll calendering is 300-320 N / mm, and the calendering rate is 2-3 m / min.

[0024] As a further technical solution, the preparation method of the copolymer toughening agent is as follows:

[0025] (1) adding butadiene, styrene and ethyl acrylate into a reaction kettle in a mass ratio of (40-60):(20-30):(20-30), adding 0.6-0.9% of the total mass of the monomer as initiator ammonium persulfate and 1-3% of the total mass of the monomer as emulsifier sodium dibutylnaphthalene sulfonate, and then adding deionized water to make the mass fraction of the monomers 30-40%;

[0026] (2) introducing nitrogen into the reactor, exhausting the air in the reactor, heating the reactor to 70-80° C., and stirring the reaction for 3-5 hours;

[0027] (3) After the reaction is completed, the mixture is naturally cooled to room temperature, and the pH value is adjusted to 8-8.5 with a sodium hydroxide solution to obtain a reactant;

[0028] (4) adding 2-5% of the mass of the reaction product of nano-attapulgite and 0.5-2% of the mass of the reaction product of silane coupling agent KH-550 to the above reaction product, stirring and mixing at 50-60° C. for 2-3 hours to uniformly disperse the nano-attapulgite and chemically bond it to the copolymer to a certain extent;

[0029] (5) The copolymer toughening agent powder is then obtained by spray drying.

[0030] As a further technical solution, the nano-attapulgite is subjected to an organic treatment before being added. The specific method is: the nano-attapulgite is dispersed in water to form a suspension with a mass fraction of 5-10%, hexadecyltrimethylammonium chloride accounting for 5-10% of the mass of the nano-attapulgite is added, and the reaction is stirred at 70-80°C for 2-3 hours, and then filtered, washed, and dried to obtain the organic nano-attapulgite.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The waterproof SPC floor prepared by the present invention has obvious advantages in environmental protection, durability, performance improvement and other aspects. The waterproof SPC floor of the present invention uses calcium carbonate powder and composite modified polyvinyl chloride resin as core raw materials, eliminates the use of harmful substances such as formaldehyde and benzene from the source, and meets the strict national environmental protection standards. The present invention significantly improves the comprehensive performance of polyvinyl chloride resin by composite modification of rosin resin, maleic anhydride and modified copolymer toughening agent with polyvinyl chloride resin. Through the addition of rosin resin, not only the flexibility of the floor is enhanced, so that it can better adapt to different use environments, but also the overall strength and toughness are improved, and the SPC floor is effectively prevented from breaking during use. Maleic anhydride, as a grafting monomer, can play the role of a bridge and a link, greatly enhances the compatibility between the components, makes the microstructure of the material more stable and tight, and can lay a solid foundation for the high performance of the floor. By adding the modified copolymer toughening agent, the impact resistance of the resin can be further improved, thereby effectively resisting external impact. Moreover, the coordination of various components can significantly improve the waterproof performance of the SPC floor.

[0033] The copolymer toughener used in the present invention is double-modified by nano-attapulgite and silane coupling agent KH-550, thereby improving the mechanical properties and durability of the material. Nano-attapulgite has a high specific surface area and a unique layered structure, and can be evenly dispersed in the polymer to form a physical cross-linked network, which can enhance the strength and rigidity of the polymer and improve the overall bearing capacity of the SPC floor. Silane coupling agent KH-550 can further improve the bonding between nano-attapulgite and the copolymer, further enhancing the stability and water resistance of the material. The SPC floor can still maintain good dimensional stability in a humid environment and is not easily affected by water erosion.

[0034] In the preparation process of the base material, the dosage of each component was adjusted and improved, so that each component can play a strong synergistic role, thereby improving the overall performance of the material. Calcium carbonate powder is used as a filler and is evenly distributed in the base material, which increases the density and hardness of the base material and effectively reduces the channels for water penetration. In addition, the composite modified polyvinyl chloride resin has certain waterproof properties, which enables the base material to better resist the invasion of water, fundamentally eliminating the problem of expansion and deformation caused by water absorption.

[0035] The nano-silica modified UV coating on the surface of the SPC floor can also improve the waterproof performance. As the main film-forming substance of the coating, polyurethane acrylate has good flexibility and wear resistance, and can form a protective film on the surface of the SPC floor. The active diluent can properly adjust the viscosity of the coating, so that it has good fluidity and construction performance, and can be evenly covered on the surface of the floor. Under the irradiation of ultraviolet light, the photoinitiator will initiate a polymerization reaction, thereby prompting the coating to cure quickly, forming a tight molecular structure, and improving densification. After the surface treatment of the nano-silica with the silane coupling agent KH-550, it can be evenly dispersed in the coating, significantly increasing the surface roughness and hydrophobicity of the coating.

[0036] In summary, the waterproof SPC floor production process of the present invention significantly improves the waterproof performance of the floor in an all-round and multi-level manner through deep modification of raw materials and coordinated cooperation of various components.

[0037] Instruction Manual

[0038] Figure 1 It is a production process flow chart of the present invention;

[0039] Figure 2 It is a bar graph of the mass change rate of each group in the test of the present invention. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The following are specific embodiments:

[0042] Example 1

[0043] The production process of waterproof SPC flooring includes the following steps:

[0044] (1) Preparation of base material: 50 parts of calcium carbonate powder, 20 parts of composite modified polyvinyl chloride resin, 5 parts of plasticizer DOTP, 2 parts of calcium zinc stabilizer, and 1 part of titanium dioxide are mixed in proportion to form an SPC base material mixture;

[0045] The calcium zinc stabilizer is a mixture of calcium stearate and zinc stearate in a mass ratio of 3:2;

[0046] The preparation method of the composite modified polyvinyl chloride resin is as follows: rosin resin is crushed into particles with a particle size of less than 1 mm; rosin resin particles and polyvinyl chloride resin are added into a high-speed mixer according to a mass ratio of polyvinyl chloride resin to rosin resin of 7:1, and stirred at a speed of 600 r / min for 5 minutes; maleic anhydride accounting for 1.5% of the mass of the polyvinyl chloride resin is added, and stirring is continued for 3 minutes; modified copolymer toughening agent is added according to a mass ratio of polyvinyl chloride resin to modified copolymer toughening agent of 12:1, and stirred at a speed of 1200 r / min for 10 minutes; the mixed materials are transferred to a hopper of a twin-screw extruder, and granulated by melt extrusion to obtain; the temperature parameters of each zone of the twin-screw extruder are specifically as follows: the temperature of the feeding section is 140°C, the temperature of the melting section is 180°C, the temperature of the homogenizing section is 175°C, the twin-screw extruder is started, and the screw speed is controlled at 60 r / min.

[0047] The preparation method of the copolymer toughening agent is as follows: butadiene, styrene and ethyl acrylate are added into a reactor in a mass ratio of 40:20:20, and at the same time, 0.6% of the total mass of the monomer as the initiator ammonium persulfate and 1% of the total mass of the monomer as the emulsifier sodium dibutylnaphthalene sulfonate are added, and then deionized water is added to make the mass fraction of the monomer 30%; nitrogen is introduced into the reactor, the air in the reactor is discharged, the reactor is heated to 70°C, and stirred for reaction for 3 hours; after the reaction is terminated, the reactor is naturally cooled to room temperature, and the pH value is adjusted to 8 with a sodium hydroxide solution to obtain a reactant; 2% of the mass of the reaction product as the nano-attapulgite and 0.5% of the mass of the reaction product as the silane coupling agent KH-550 are added to the above reaction product, and the mixture is stirred and mixed at 50°C for 2 hours to make the nano-attapulgite uniformly dispersed and chemically bonded to the copolymer to a certain extent; and then the copolymer toughening agent powder is obtained by spray drying;

[0048] The nano-attapulgite is organically treated before being added. The specific method is: disperse the nano-attapulgite in water to form a suspension with a mass fraction of 5%, add hexadecyltrimethylammonium chloride accounting for 5% of the mass of the nano-attapulgite, stir and react at 70°C for 2 hours, and then filter, wash and dry to obtain the organic nano-attapulgite.

[0049] (2) high-temperature extrusion molding: the mixed material of step (1) is melt-blended by a twin-screw extruder, extruded through a die to form an SPC substrate layer, a colored decorative film is attached to the surface, the colored film is closely attached to the substrate by hot pressing, and a wear-resistant layer is attached on the colored film, the wear-resistant layer is made of polyvinyl chloride resin and nano-alumina mixed in a mass ratio of 10:1 to obtain a slab; the temperature of each zone of the twin-screw extruder is 160°C for the feeding section, 195°C for the melting section, and 190°C for the homogenizing section; the twin-screw extruder is started, and the screw speed is controlled at 80r / min;

[0050] (3) Calendering and cooling: The slab prepared as above was subjected to three-roll calendering treatment, and the roller temperature was adjusted to 110°C, and then cooled to below 38°C through a water cooling system; the line pressure of the three-roll calendering was 320N / mm, and the calendering rate was 3m / min.

[0051] (4) Surface treatment: A nano-silica modified UV coating is applied on the surface of the wear-resistant layer, and a hydrophobic surface is formed after UV curing, and then tempering is performed. During the tempering process, the hot water temperature is controlled at 80°C and the cold water temperature is 10°C; the coating amount of the nano-silica modified UV coating is 8g / m 2 , surface contact angle after curing ≥115°;

[0052] The raw material components of the nano-silica modified UV coating include, by mass, 30 parts of polyurethane acrylate, 20 parts of active diluent, 2 parts of photoinitiator, and 10 parts of nano-silica; the active diluent is β-hydroxyethyl methacrylate, the particle size of the nano-silica is 10 nm, and the surface is treated with a silane coupling agent KH-550, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the UV curing process parameters are as follows: the UV wavelength is 320 nm; the UV radiation intensity is 700 mW / cm 2 ; Curing time is 15s;

[0053] (5) Cutting and locking processing: The required floor size is obtained through cutting, and a two-way locking structure is processed on the edge. After passing the inspection and packaging, the finished product is obtained.

[0054] Example 2

[0055] The production process of waterproof SPC flooring includes the following steps:

[0056] (1) Preparation of base material: 53 parts of calcium carbonate powder, 23 parts of composite modified polyvinyl chloride resin, 6 parts of plasticizer DOTP, 2.5 parts of calcium zinc stabilizer, and 1.2 parts of titanium dioxide are mixed in proportion to form an SPC base material mixture;

[0057] The calcium zinc stabilizer is a mixture of calcium stearate and zinc stearate in a mass ratio of 3:2;

[0058] The preparation method of the composite modified polyvinyl chloride resin is as follows: rosin resin is crushed into particles with a particle size of less than 1 mm; rosin resin particles and polyvinyl chloride resin are added into a high-speed mixer according to a mass ratio of polyvinyl chloride resin to rosin resin of 8:1.5, and stirred at a speed of 650 r / min for 6 minutes; maleic anhydride accounting for 1.6% of the mass of the polyvinyl chloride resin is added, and stirring is continued for 3.5 minutes; modified copolymer toughening agent is added according to a mass ratio of polyvinyl chloride resin to modified copolymer toughening agent of 13:1.5, and stirred at a speed of 1300 r / min for 12 minutes; the mixed materials are transferred to a hopper of a twin-screw extruder, and granulated by melt extrusion to obtain; the temperature parameters of each zone of the twin-screw extruder are specifically as follows: the temperature of the feeding section is 140°C, the temperature of the melting section is 180°C, the temperature of the homogenizing section is 175°C, the twin-screw extruder is started, and the screw speed is controlled at 60 r / min.

[0059] The preparation method of the copolymer toughening agent is as follows: butadiene, styrene and ethyl acrylate are added to a reactor in a mass ratio of 45:22:22, and at the same time, ammonium persulfate as an initiator accounting for 0.8% of the total mass of the monomers and sodium dibutylnaphthalene sulfonate as an emulsifier accounting for 1.5% of the total mass of the monomers are added, and deionized water is added to make the mass fraction of the monomers 33%; nitrogen is introduced into the reactor, the air in the reactor is discharged, the reactor is heated to 73°C, and the reaction is stirred for 3.5 hours; after the reaction is terminated, it is naturally cooled to room temperature, and the pH value is adjusted to 8.5 with a sodium hydroxide solution to obtain a reactant; nano-attapulgite accounting for 3% of the mass of the reaction product and silane coupling agent KH-550 accounting for 1% of the mass of the reaction product are added to the above reaction product, and the mixture is stirred and mixed at 53°C for 2.2 hours to make the nano-attapulgite uniformly dispersed and chemically bonded to the copolymer to a certain extent; and then the copolymer toughening agent powder is obtained by spray drying;

[0060] The nano-attapulgite is organically treated before being added. The specific method is: disperse the nano-attapulgite in water to form a suspension with a mass fraction of 6%, add hexadecyltrimethylammonium chloride accounting for 6% of the mass of the nano-attapulgite, stir and react at 73°C for 2.2 hours, and then filter, wash and dry to obtain the organic nano-attapulgite.

[0061] (2) high-temperature extrusion molding: the mixed material of step (1) is melt-blended by a twin-screw extruder, extruded through a die to form an SPC substrate layer, a colored decorative film is attached to the surface, the colored film is closely attached to the substrate by hot pressing, and a wear-resistant layer is attached on the colored film, the wear-resistant layer is made of polyvinyl chloride resin and nano-alumina mixed in a mass ratio of 10:1 to obtain a slab; the temperature of each zone of the twin-screw extruder is 160°C for the feeding section, 195°C for the melting section, and 190°C for the homogenizing section; the twin-screw extruder is started, and the screw speed is controlled at 80r / min;

[0062] (3) Calendering and cooling: The slab prepared as above was subjected to three-roll calendering treatment, and the roller temperature was adjusted to 115°C, and then cooled to below 38°C through a water cooling system; the line pressure of the three-roll calendering was 320N / mm, and the calendering rate was 3m / min.

[0063] (4) Surface treatment: A nano-silica modified UV coating is applied on the surface of the wear-resistant layer, and a hydrophobic surface is formed after UV curing, and then tempering is performed. During the tempering process, the hot water temperature is controlled at 90°C and the cold water temperature is 10°C; the coating amount of the nano-silica modified UV coating is 9g / m 2 , surface contact angle after curing ≥115°;

[0064] The raw material components of the nano-silica modified UV coating include, by weight: 33 parts of polyurethane acrylate, 23 parts of active diluent, 2.5 parts of photoinitiator, and 12 parts of nano-silica; the active diluent is β-hydroxyethyl methacrylate, the particle size of the nano-silica is 10 nm, and the surface is treated with a silane coupling agent KH-550, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the UV curing process parameters are as follows: the UV wavelength is 340 nm; the UV radiation intensity is 750 mW / cm 2 ; Curing time is 16s;

[0065] (5) Cutting and locking processing: The required floor size is obtained through cutting, and a two-way locking structure is processed on the edge. After passing the inspection and packaging, the finished product is obtained.

[0066] Example 3

[0067] The production process of waterproof SPC flooring includes the following steps:

[0068] (1) Preparation of base material: 57 parts of calcium carbonate powder, 27 parts of composite modified polyvinyl chloride resin, 7 parts of plasticizer DOTP, 3.5 parts of calcium zinc stabilizer, and 1.8 parts of titanium dioxide are mixed in proportion to form an SPC base material mixture;

[0069] The calcium zinc stabilizer is a mixture of calcium stearate and zinc stearate in a mass ratio of 3:2;

[0070] The preparation method of the composite modified polyvinyl chloride resin is as follows: rosin resin is crushed into particles with a particle size of less than 1 mm; rosin resin particles and polyvinyl chloride resin are added into a high-speed mixer according to a mass ratio of polyvinyl chloride resin to rosin resin of 9:2.5, and stirred at a speed of 750 r / min for 9 minutes; maleic anhydride accounting for 1.9% of the mass of the polyvinyl chloride resin is added, and stirring is continued for 4.5 minutes; modified copolymer toughening agent is added according to a mass ratio of polyvinyl chloride resin to modified copolymer toughening agent of 14:2.5, and stirred at a speed of 1400 r / min for 14 minutes; the mixed materials are transferred to a hopper of a twin-screw extruder, and granulated by melt extrusion to obtain; the temperature parameters of each zone of the twin-screw extruder are specifically as follows: the temperature of the feeding section is 140°C, the temperature of the melting section is 180°C, the temperature of the homogenizing section is 175°C, the twin-screw extruder is started, and the screw speed is controlled at 60 r / min.

[0071] The preparation method of the copolymer toughening agent is as follows: butadiene, styrene and ethyl acrylate are added to a reactor in a mass ratio of 55:28:28, and at the same time, an initiator ammonium persulfate accounting for 0.7% of the total mass of the monomers and an emulsifier sodium dibutylnaphthalene sulfonate accounting for 2.5% of the total mass of the monomers are added, and deionized water is added to make the mass fraction of the monomers 37%; nitrogen is introduced into the reactor, the air in the reactor is discharged, the reactor is heated to 77°C, and the reaction is stirred for 4.5 hours; after the reaction is terminated, the reactor is naturally cooled to room temperature, and the pH value is adjusted to 8.2 with a sodium hydroxide solution to obtain a reactant; nano-attapulgite accounting for 4% of the mass of the reaction product and silane coupling agent KH-550 accounting for 1.5% of the mass of the reaction product are added to the above reaction product, and the mixture is stirred and mixed at 57°C for 2.8 hours to make the nano-attapulgite uniformly dispersed and chemically bonded to the copolymer to a certain extent; and then the copolymer toughening agent powder is obtained by spray drying;

[0072] The nano-attapulgite is organically treated before being added. The specific method is: disperse the nano-attapulgite in water to form a suspension with a mass fraction of 9%, add hexadecyltrimethylammonium chloride accounting for 9% of the mass of the nano-attapulgite, stir and react at 77°C for 2.8 hours, and then filter, wash and dry to obtain the organic nano-attapulgite.

[0073] (2) high-temperature extrusion molding: the mixed material of step (1) is melt-blended by a twin-screw extruder, extruded through a die to form an SPC substrate layer, a colored decorative film is attached to the surface, the colored film is closely attached to the substrate by hot pressing, and a wear-resistant layer is attached on the colored film, the wear-resistant layer is made of polyvinyl chloride resin and nano-alumina mixed in a mass ratio of 10:1 to obtain a slab; the temperature of each zone of the twin-screw extruder is 160°C for the feeding section, 195°C for the melting section, and 190°C for the homogenizing section; the twin-screw extruder is started, and the screw speed is controlled at 80r / min;

[0074] (3) Calendering and cooling: The slab prepared as above was subjected to three-roll calendering treatment, and the roller temperature was adjusted to 125°C, and then cooled to below 38°C through a water cooling system; the line pressure of the three-roll calendering was 320N / mm, and the calendering rate was 3m / min.

[0075] (4) Surface treatment: A nano-silica modified UV coating is applied on the surface of the wear-resistant layer, and a hydrophobic surface is formed after UV curing, and then tempering is performed. During the tempering process, the hot water temperature is controlled at 110°C and the cold water temperature is 10°C; the coating amount of the nano-silica modified UV coating is 11g / m 2 , surface contact angle after curing ≥115°;

[0076] The raw material components of the nano-silica modified UV coating include, by mass, 37 parts of polyurethane acrylate, 27 parts of active diluent, 3.5 parts of photoinitiator, and 15 parts of nano-silica; the active diluent is β-hydroxyethyl methacrylate, the particle size of the nano-silica is 10 nm, and the surface is treated with a silane coupling agent KH-550, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the UV curing process parameters are as follows: the UV wavelength is 380 nm; the UV radiation intensity is 750 mW / cm 2 ; Curing time is 19s;

[0077] (5) Cutting and locking processing: The required floor size is obtained through cutting, and a two-way locking structure is processed on the edge. After passing the inspection and packaging, the finished product is obtained.

[0078] Example 4

[0079] The production process of waterproof SPC flooring includes the following steps:

[0080] (1) Preparation of base material: 60 parts of calcium carbonate powder, 30 parts of composite modified polyvinyl chloride resin, 8 parts of plasticizer DOTP, 4 parts of calcium zinc stabilizer, and 2 parts of titanium dioxide are mixed in proportion to form an SPC base material mixture;

[0081] The calcium zinc stabilizer is a mixture of calcium stearate and zinc stearate in a mass ratio of 3:2;

[0082] The preparation method of the composite modified polyvinyl chloride resin is as follows: rosin resin is crushed into particles with a particle size of less than 1 mm; rosin resin particles and polyvinyl chloride resin are added into a high-speed mixer according to a mass ratio of polyvinyl chloride resin to rosin resin of 10:3, and stirred at a speed of 800 r / min for 10 minutes; maleic anhydride accounting for 2% of the mass of the polyvinyl chloride resin is added, and stirring is continued for 5 minutes; modified copolymer toughening agent is added according to a mass ratio of polyvinyl chloride resin to modified copolymer toughening agent of 15:3, and stirred at a speed of 1500 r / min for 15 minutes; the mixed materials are transferred to a hopper of a twin-screw extruder, and granulated by melt extrusion to obtain; the temperature parameters of each zone of the twin-screw extruder are specifically as follows: the temperature of the feeding section is 140°C, the temperature of the melting section is 180°C, the temperature of the homogenizing section is 175°C, the twin-screw extruder is started, and the screw speed is controlled at 60 r / min.

[0083] The preparation method of the copolymer toughening agent is as follows: butadiene, styrene and ethyl acrylate are added to a reactor in a mass ratio of 60:30:30, and at the same time, an initiator ammonium persulfate accounting for 0.9% of the total mass of the monomers and an emulsifier sodium dibutylnaphthalene sulfonate accounting for 3% of the total mass of the monomers are added, and then deionized water is added to make the mass fraction of the monomers 40%; nitrogen is introduced into the reactor, the air in the reactor is discharged, the reactor is heated to 80°C, and stirred for reaction for 5 hours; after the reaction is terminated, it is naturally cooled to room temperature, and the pH value is adjusted to 8.5 with a sodium hydroxide solution to obtain a reactant; nano-attapulgite accounting for 5% of the mass of the reaction product and a silane coupling agent KH-550 accounting for 2% of the mass of the reaction product are added to the above reaction product, and the mixture is stirred and mixed at 60°C for 3 hours to make the nano-attapulgite uniformly dispersed and chemically bonded to the copolymer to a certain extent; and then the copolymer toughening agent powder is obtained by spray drying;

[0084] The nano-attapulgite is organically treated before being added. The specific method is: disperse the nano-attapulgite in water to form a suspension with a mass fraction of 10%, add hexadecyltrimethylammonium chloride accounting for 10% of the mass of the nano-attapulgite, stir and react at 80°C for 3 hours, and then filter, wash and dry to obtain the organic nano-attapulgite.

[0085] (2) high-temperature extrusion molding: the mixed material of step (1) is melt-blended by a twin-screw extruder, extruded through a die to form an SPC substrate layer, a colored decorative film is attached to the surface, the colored film is closely attached to the substrate by hot pressing, and a wear-resistant layer is attached on the colored film, the wear-resistant layer is made of polyvinyl chloride resin and nano-alumina mixed in a mass ratio of 10:1 to obtain a slab; the temperature of each zone of the twin-screw extruder is 160°C for the feeding section, 195°C for the melting section, and 190°C for the homogenizing section; the twin-screw extruder is started, and the screw speed is controlled at 80r / min;

[0086] (3) Calendering and cooling: The slab prepared as above was subjected to three-roll calendering treatment, and the roller temperature was adjusted to 130°C, and then cooled to below 38°C through a water cooling system; the line pressure of the three-roll calendering was 320N / mm, and the calendering rate was 3m / min.

[0087] (4) Surface treatment: A nano-silica modified UV coating is applied on the surface of the wear-resistant layer, and a hydrophobic surface is formed after UV curing, and then tempering is performed. During the tempering process, the hot water temperature is controlled at 120°C and the cold water temperature is 10°C; the coating amount of the nano-silica modified UV coating is 12g / m 2 , surface contact angle after curing ≥115°;

[0088] The raw material components of the nano-silica modified UV coating include, by mass, 40 parts of polyurethane acrylate, 30 parts of active diluent, 4 parts of photoinitiator, and 16 parts of nano-silica; the active diluent is β-hydroxyethyl methacrylate, the particle size of the nano-silica is 10nm, and the surface is treated with a silane coupling agent KH-550, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the UV curing process parameters are as follows: the UV wavelength is 400nm; the UV radiation intensity is 700mW / cm 2 ; Curing time is 20s;

[0089] (5) Cutting and locking processing: The required floor size is obtained through cutting, and a two-way locking structure is processed on the edge. After passing the inspection and packaging, the finished product is obtained.

[0090] Comparative Example 1

[0091] Preparation of base material: 50 parts of calcium carbonate powder, 20 parts of unmodified polyvinyl chloride resin, 5 parts of plasticizer DOTP, 2 parts of calcium zinc stabilizer, and 1 part of titanium dioxide are mixed in proportion to form an SPC base material mixture.

[0092] Subsequent steps: Same as Example 1.

[0093] Comparative Example 2

[0094] Preparation of base material: 50 parts of calcium carbonate powder, 20 parts of composite modified polyvinyl chloride resin, 5 parts of plasticizer DOTP, 2 parts of calcium zinc stabilizer, and 1 part of titanium dioxide are mixed in proportion to form an SPC base material mixture. No copolymer toughening agent is added in the preparation of composite modified polyvinyl chloride resin.

[0095] Subsequent steps: Same as Example 1.

[0096] Comparative Example 3

[0097] Preparation of copolymer toughening agent: butadiene, styrene and ethyl acrylate are added to the reactor in a mass ratio of 40:20:20, and ammonium persulfate, an initiator, accounting for 0.5% of the total mass of the monomers and sodium dibutylnaphthalene sulfonate, an emulsifier, accounting for 1% of the total mass of the monomers are added at the same time, and deionized water is added to make the mass fraction of the monomers 30%. Nitrogen is introduced into the reactor, and the air in the reactor is discharged. The reactor is heated to 70°C and stirred for 3 hours. After the reaction is terminated, it is naturally cooled to room temperature, and the pH value is adjusted to 7 with sodium hydroxide solution. The copolymer toughening agent powder is directly obtained by spray drying without modification of nano-attapulgite and silane coupling agent KH-550.

[0098] Preparation of base material and subsequent steps: the same as in Example 1.

[0099] test:

[0100] Waterproof performance test

[0101] Test method: Using an immersion test, the SPC floor samples prepared in Examples 1-4 and Comparative Examples 1-3 were cut into squares of 80 mm × 80 mm and placed in a water tank filled with water to completely immerse the samples. The water temperature was maintained at 25 ± 1 ° C. After immersion for 3 days, the samples were taken out, the surface moisture was absorbed with filter paper, and the samples were weighed immediately to calculate the mass change rate before and after immersion.

[0102] Calculation formula: mass change rate (%) = (mass after immersion - mass before immersion) / mass before immersion × 100%;

[0103] Table 1

[0104] Quality change rate % Example 1 0.25 Example 2 0.21 Example 3 0.29 Example 4 0.31 Comparative Example 1 2.33 Comparative Example 2 1.56 Comparative Example 3 0.67

[0105] It can be seen from Table 1 that the SPC floor prepared in the present invention has excellent waterproof performance.

[0106] Wear resistance test

[0107] Test method: Use a wear tester and the wear resistance test method specified in GB / T18102-2020 "Impregnated Paper Laminated Wood Flooring". Load a certain pressure on the sample surface, make the grinding wheel rotate and rub on the sample surface for a certain number of revolutions (5000 revolutions), and then measure the mass change of the sample surface before and after abrasion;

[0108] Calculation formula: Wear loss (g / cm 2 ) = (mass before abrasion - mass after abrasion) / sample area;

[0109] Table 2

[0110]

[0111]

[0112] It can be seen from Table 2 that the SPC floor prepared by the present invention has excellent wear resistance.

[0113] Impact resistance test

[0114] Test method: Use a falling ball impact test, place the sample horizontally on a rigid support table, use a 1kg steel ball to freely drop from a height of 1m to impact the sample surface, and observe whether there are cracks or damage on the sample surface. Each sample is subjected to 5 impact tests, and the number of damages is recorded.

[0115] Evaluation criteria: The fewer the number of breakages, the better the impact resistance;

[0116] Table 3

[0117] Impact damage resistance times / times Example 1 0 Example 2 0 Example 3 0 Example 4 0 Comparative Example 1 3 Comparative Example 2 2 Comparative Example 3 1

[0118] It can be seen from Table 3 that the SPC floor prepared by the present invention has excellent impact resistance.

[0119] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all details in detail, nor do they limit the invention to only the specific embodiments described. Obviously, many modifications and changes can be made according to the content of this specification.

Claims

1. The production process of waterproof SPC floor is characterized by: The following steps are involved: (1) Preparation of base material: Calcium carbonate powder, composite modified polyvinyl chloride resin, plasticizer DOTP, calcium zinc stabilizer, and titanium dioxide are mixed in proportion to form an SPC base material mixture; The calcium zinc stabilizer is a mixture of calcium stearate and zinc stearate in a mass ratio of 3:2; (2) high-temperature extrusion molding: the mixed material of step (1) is melt-blended by a twin-screw extruder, extruded through a die to form an SPC substrate layer, a colored decorative film is attached to the surface, the colored film is closely attached to the substrate by hot pressing, and a wear-resistant layer is attached on the colored film, the wear-resistant layer is made of polyvinyl chloride resin and nano-alumina mixed in a mass ratio of 10:1, and a slab is obtained; (3) Calendering and cooling: The slab prepared above is subjected to a three-roll calendering process, the roller temperature is adjusted to 110-130° C., and then cooled by a water cooling system to below 38° C.; (4) Surface treatment: A nano-silicon dioxide modified UV coating is applied to the surface of the wear-resistant layer, and a hydrophobic surface is formed after UV curing, and then a tempering treatment is performed. During the tempering process, the hot water temperature is controlled at 80-120°C and the cold water temperature is 10°C; (5) Cutting and locking processing: The required floor size is obtained through cutting, and a two-way locking structure is processed on the edge. After passing the inspection and packaging, the finished product is obtained.

2. The production process of the waterproof SPC floor according to claim 1 is characterized in that: The raw materials of the SPC substrate mixture in step (1) include, by weight: 50-60 parts of calcium carbonate powder, 20-30 parts of composite modified polyvinyl chloride resin, 5-8 parts of plasticizer DOTP, 2-4 parts of calcium zinc stabilizer, and 1-2 parts of titanium dioxide.

3. The production process of the waterproof SPC floor according to claim 2 is characterized in that: The preparation method of the composite modified polyvinyl chloride resin comprises the following steps: crushing rosin resin into particles with a particle size of less than 1 mm; adding rosin resin particles and polyvinyl chloride resin into a high-speed mixer in a mass ratio of 7-10:1-3 of polyvinyl chloride resin to rosin resin, and stirring at a speed of 600-800 r / min for 5-10 minutes; adding maleic anhydride accounting for 1.5-2% of the mass of the polyvinyl chloride resin, and continuing stirring for 3-5 minutes; adding modified copolymer toughening agent in a mass ratio of 12-15:1-3 of polyvinyl chloride resin to modified copolymer toughening agent, and stirring at a speed of 1200-1500 r / min for 10-15 minutes; transferring the mixed materials into a hopper of a twin-screw extruder, and performing melt extrusion granulation to obtain; The specific temperature parameters of each zone of the twin-screw extruder are as follows: the temperature of the feeding section is 140-145°C, the temperature of the melting section is 180-190°C, and the temperature of the homogenizing section is 175-180°C. The twin-screw extruder is started and the screw speed is controlled at 60-70r / min.

4. The production process of the waterproof SPC floor according to claim 1, characterized in that: In the step (2), the temperature of each zone of the twin-screw extruder is 155-160°C in the feeding section, 188-195°C in the melting section, and 185-190°C in the homogenizing section. The twin-screw extruder is started and the screw speed is controlled at 80r / min.

5. The production process of the waterproof SPC floor according to claim 1 is characterized in that: The coating amount of the nano-silicon dioxide modified UV coating in step (4) is 8-12 g / m 2 ; The raw material components of the nano-silicon dioxide modified UV coating include, by weight: 30-40 parts of polyurethane acrylate, 20-30 parts of active diluent, 2-4 parts of photoinitiator, and 10-16 parts of nano-silicon dioxide; The active diluent is methacrylate-β-hydroxyethyl ester, the particle size of the nano silicon dioxide is 10-20nm and is surface treated with a silane coupling agent KH-550, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

6. The production process of the waterproof SPC floor according to claim 5, characterized in that: The UV curing process parameters are as follows: UV wavelength is 320-400nm; UV radiation intensity is 700-750mW / cm 2 ; Curing time is 15-20s.

7. The production process of the waterproof SPC floor according to claim 1, characterized in that: In the step (3), the line pressure of the three-roll calendering is 300-320 N / mm, and the calendering rate is 2-3 m / min.

8. The production process of the waterproof SPC floor according to claim 3, characterized in that: The preparation method of the copolymer toughening agent is as follows: (1) adding butadiene, styrene and ethyl acrylate into a reaction kettle in a mass ratio of (40-60):(20-30):(20-30), adding 0.6-0.9% of the total mass of the monomer as initiator ammonium persulfate and 1-3% of the total mass of the monomer as emulsifier sodium dibutylnaphthalene sulfonate, and then adding deionized water to make the mass fraction of the monomers 30-40%; (2) introducing nitrogen into the reactor, exhausting the air in the reactor, heating the reactor to 70-80° C., and stirring the reaction for 3-5 hours; (3) After the reaction is completed, the mixture is naturally cooled to room temperature, and the pH value is adjusted to 8-8.5 with a sodium hydroxide solution to obtain a reactant; (4) adding 2-5% of the mass of the reaction product of nano-attapulgite and 0.5-2% of the mass of the reaction product of silane coupling agent KH-550 to the above reaction product, stirring and mixing at 50-60° C. for 2-3 hours; (5) The copolymer toughening agent powder is then obtained by spray drying.

9. The production process of the waterproof SPC floor according to claim 8, characterized in that: The nano-attapulgite is organically treated before being added, and the specific method is: disperse the nano-attapulgite in water to form a suspension with a mass fraction of 5-10%, add hexadecyltrimethylammonium chloride accounting for 5-10% of the mass of the nano-attapulgite, stir and react at 70-80°C for 2-3 hours, and then filter, wash and dry to obtain the organic nano-attapulgite.

Citation Information

Patent Citations

  • SPC floor

    CN113150466A

Cited By

  • Production process of WPC mould pressing floor

    CN120481343A

  • A production process of WPC molded floor

    CN120481343B